1989
DOI: 10.1126/science.2473529
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Transcription Enhancement by Purified Derivatives of the Glucocorticoid Receptor

Abstract: Mammalian glucocorticoid receptors enhance transcription from linked promoters by binding to glucocorticoid response element (GRE) DNA sequences. Understanding the mechanism of receptor action will require biochemical studies with purified components. Enhancement was observed in vitro with derivatives of the receptor that were expressed in Escherichia coli, purified, and added to a cell-free extract from Drosophila embryo nuclei. Transcription from promoters linked to one or multiple GREs was selectively enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…netically map an enhancement region [enhl] within the finger domain, extending the findings that this portion of the receptor alone is sufficient for enhancement, al beit with substantially reduced activity, both in vivo ) and in vitro (Freedman et al 1989). In this regard, it is particularly intriguing that deletion mutagenesis (Giguere et al 1986), as well as direct ac tivity assays , identified a second enhancement region, enh2, near the amino terminus of the receptor, and other work has inferred yet another distinct enhancement region within the receptor (Hollenberg and Evans 1988; see also Godowski et al 1988).…”
Section: Discussionmentioning
confidence: 70%
“…netically map an enhancement region [enhl] within the finger domain, extending the findings that this portion of the receptor alone is sufficient for enhancement, al beit with substantially reduced activity, both in vivo ) and in vitro (Freedman et al 1989). In this regard, it is particularly intriguing that deletion mutagenesis (Giguere et al 1986), as well as direct ac tivity assays , identified a second enhancement region, enh2, near the amino terminus of the receptor, and other work has inferred yet another distinct enhancement region within the receptor (Hollenberg and Evans 1988; see also Godowski et al 1988).…”
Section: Discussionmentioning
confidence: 70%
“…Beads were washed three times in pull-down buffer and then incubated with 4 g of GR fragment EX556 (Freedman et al, 1989) containing NL1 for 3 h at 4°C. Bound proteins were resolved and immunoblotted with the BuGR2 antibody.…”
Section: Binding Assaysmentioning
confidence: 99%
“…To create an in-frame fusion, these intermediate plasmids were restricted with XmaI and XhoI, filled in with Klenow, and religated to yield pETI407-5251-HMK and pET(407-525-K461Aj-HMK. Finally, a BstBI-XbaI fragment from T7-EX556 (Freedman et al 1989) was cloned into the BstBI and XbaI sites of pET(407-525t HMK and pET[407-525-K461Al-HMK to create PET-EX525-HMK and PET-EX525(K461AtHMK. The resulting derivatives have a 5 amino-acid heart muscle kinase site (Arg-Arg-AlaSer-Val) fused at their carboxyl termini.…”
Section: Plasmidsmentioning
confidence: 99%
“…Protein purification EX525-HMK and EX525(K461A)-HMK were overexpressed in, and purified from, the BL21/DE3 strain of Escherichia coli as described previously (Freedman et al 1989) except that only one column, CM-Sepharose, was used. Briefly, the cell pellets were processed as described and dialyzed in HZ buffer [lo% glycerol, 50 mM HEPES (pH 8.0), 0.5 mM EDTA] to 50 mM NaC1.…”
Section: Plasmidsmentioning
confidence: 99%